Blended Learning with schoology in impulse and momentum materials: The development of physics teaching materials - Noor, Ricky Nugraha Fitrian; Zainuddin, Zainuddin; Misbah, Misbah; Hartini, Sri; Dewantara, Dewi (Online Learning In Educational Research (OLER), 2021)
Information Technology Integration in the physics learning process has not happened optimally. Therefore, a study was conducted, which aims to describe the feasibility of physics teaching materials based on blended-learning with Schoology in subject matter impulses and momentum. This research is research and development using the ADDIE model. The trial subjects in this study were 28 students of class XI in one of the Vocational Schools in the city of Banjarmasin. The instruments used were media validation sheets, lesson plan implementation sheets, and learning outcome tests. Data is then analyzed descriptively quantitatively. The results of the study state that the learning materials developed 1) was valid, sourced from the results of the validation sheet, 2) was practical, based on the lesson plan implementation sheet, and 3) was effective in improving learning outcomes, seen from the results of the N-gain test. It can be concluded that physics teaching materials based on blended learning with Schoology that are developed are feasible to use in subject matter impulses and momentum. Teaching materials integrated with Schoology can be used as an alternative learning solution to improve the quality of blended learning.